0
$\begingroup$

I have no idea how to solve the system below

\begin{cases} f_x = - 2 x y + y^{2} + 1 = 0 \\ f_y = - x^{2} + 2 x y - 1 = 0 \end{cases}

I began by using this linear combination $c_1 f_x + c_2 f_y = 0$ for $c_1,c_2 \in \mathbb{R}$. I set $c_1 = 1$ and $c_2 = 1$ and I got $$y^2 - x^2 - 0$$. It seems to be that this equation have infinite solutions: $(-1,-1), (0,0), (1,1), (2,2), ...$. Is my reasoning correct? When I feed the system to computer, I got $\left(1, 1\right)$ and $\left(-1, -1\right)$ as only solutions. I don't understand why.

$\endgroup$
1
  • 1
    $\begingroup$ While any solution to the original equations must also be a solution to $y^2-x^2=0$, not every solution to the latter is also a solution to the original system. For example, as you note $x=y=0$ is a solution to the latter; but it is not a solution to $f_x=0$. You have more work still to be done. $\endgroup$ Oct 4 '21 at 4:32
0
$\begingroup$

$$f_x = - 2 x y + y^{2} + 1 = 0 \tag 1$$ $$f_y = - x^{2} + 2 x y - 1 = 0 \tag 2$$

Since $y=0$ cannot be a solution (check it for $(1)$), then $$f_x =0 \implies x=\frac{y^2+1}{2 y}\tag 3$$ Plug in $(2)$ to get $$y^2-\frac{\left(y^2+1\right)^2}{4 y^2}=0\implies 3 y^4-2 y^2-1=0 \tag 4$$ $$3 y^4-2 y^2-1=(y-1) (y+1) \left(3 y^2+1\right)$$ So, the only solutions of $(4)$ are $y=\pm1$ and, back to $(3)$, $x=\pm 1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.